2008
DOI: 10.1111/j.1600-0501.2008.01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous progression of peri‐implantitis at different types of implants. An experimental study in dogs. I: clinical and radiographic observations

Abstract: Spontaneous progression of experimentally induced peri-implantitis occurred at implants with different geometry and surface characteristics. Progression was most pronounced at implants of type D (TiUnite surface).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
167
6
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(189 citation statements)
references
References 17 publications
12
167
6
4
Order By: Relevance
“…Increases in surface roughness and surface free energy have been shown to facilitate microbial biofilm formation on dental implant and abutment surfaces. 51,52 The outcomes reported from experimental studies in dogs suggest that the progression of peri-implantitis, if left untreated, differs among implant types 53,54 and is more pronounced for implants with a moderately rough surface (e.g. sand-blasted and acid-etched) compared with implants with a turned surface.…”
Section: Discussionmentioning
confidence: 97%
“…Increases in surface roughness and surface free energy have been shown to facilitate microbial biofilm formation on dental implant and abutment surfaces. 51,52 The outcomes reported from experimental studies in dogs suggest that the progression of peri-implantitis, if left untreated, differs among implant types 53,54 and is more pronounced for implants with a moderately rough surface (e.g. sand-blasted and acid-etched) compared with implants with a turned surface.…”
Section: Discussionmentioning
confidence: 97%
“…Another distinct feature in studies on experimentally induced peri-implantitis was that following ligature removal, there was spontaneous continuous progression of the disease with additional bone loss. 33,38,39 All implants appear to be susceptible to peri-implantitis. 38,39 Hence, the primary objective for treating peri-implantitis is similar to that for treating peri-implant mucositis, which is the elimination of the biofilm from the implant surface.…”
Section: Etiologies and Pathogenesismentioning
confidence: 99%
“…While the TPS surface has S a values of approximately 3.1 lm, SLA has S a values of approximately 2.0 lm (Buser et al 1999). The lower microroughness should be particularly important in PCP, because it is suggested that peri-implantitis is influenced by surface characteristics (Berglundh et al 2007;Albouy et al 2008Albouy et al , 2009. However, caution is needed comparing the present study with the previous ones (Roccuzzo et al 2010(Roccuzzo et al , 2012, because of stricter plaque regimen entry level (FMPS ≤ 15% vs. FMPS ≤ 25%).…”
mentioning
confidence: 63%